Pseudomonas syringae colonizes distant tissues in Nicotiana benthamiana through xylem vessels. - Misas-Villamil, J; Kolodziejek, I; van der Hoorn, R (2011)
The ability to move from the primary infection site and colonize distant tissue in the leaf is an important property of bacterial plant pathogens, yet this aspect has hardly been investigated for model pathogens. Here we show that GFP-expressing Pseudomonas syringae pv. syringae DC3000 that lacks the HopQ1-1 effector (PtoDC3000ΔhQ) has a strong capacity to colonize distant leaf tissue from wound-inoculated sites in N. benthamiana. Distant colonization occurs within 1 week after toothpick inoculation and is characterized by distant colonies in the apoplast along the vasculature. Distant colonization is blocked by the non-host resistance response triggered by HopQ1-1 in an SGT1-dependent manner and is associated with an explosive growth of the bacterial population, and displays robust growth differences between compatible and incompatible interactions. Scanning electron microscopy revealed that PtoDC3000ΔhQ bacteria are present in xylem vessels, indicating that they use the xylem to move through the leaf blade. Distant colonization does not require flagellin-mediated motility, and is common for P. syringae pathovars that represent different phylogroups.